The Impact of Accounting Disclosure of Sustainable Development Dimensions on the Quality of Financial Reports in Libyan Commercial Banks. (Economic studies journal, 2025)
The study aimed to identify the impact of accounting disclosure regarding the dimensions of sustainable development (economic, social, environmental, technological) on the quality of financial reporting in Libyan commercial banks. To achieve this goal, the study relied on a descriptive-analytical approach, using a structured questionnaire based on an established scale. The questionnaire was distributed to bank managers, their assistants, and financial employees within the study sample. A total of 63 questionnaires were distributed, of which 56 were returned, resulting in a response rate of 88.8%.The study concluded with several findings, the most important of which is that the disclosure of sustainable development dimensions positively affects the quality of financial reports in Libyan commercial banks, particularly the social and technological dimensions. The results showed a strong correlation between the disclosure of these two dimensions (social and technological) and the quality of financial reports. Based on these findings, the study recommended enhancing the level of accounting disclosure regarding sustainable development dimensions in Libyan commercial banks and adopting standardized accounting disclosure criteria to ensure a higher level of transparency and credibility.
Keywords: Accounting Disclosure; Sustainable Development Dimensions; Financial Report Quality; Commercial Banks